La inconsistente ley de inquilinato, en relación al cobro de garantías de arrendamiento de viviendas en el Ecuador - Ramos Barreno, Carmita Oliva (2014)
In my withdrawn quality of the Race of Right in the Modality of remote Studies and it jeopardize with the culture, with Social and the Administrative thing of the National University of Loja; and, worried about the lack of guarantees that allow to regulate the fulfillment of contracts of renting for houses, I allow myself to present/display the titled work of investigation “ NECESSITY TO REGULATE IN the TENANCY LAW, the COLLECTION OF GUARANTEES BY CONCEPT OF RENTING OF HOUSES IN ECUADOR ”, with which I demonstrate the problems derived from the emptiness that exists in the Law of Tenancy, when unprotected leaving to the renter in the collection of the renting canons, as well as in the fulfillment of the contractual clauses, reason why becomes necessary to establish the collection of guarantees. The problem is of great legal significance, because we live it every day, and because it is part of the problem of the legal sciences, within the positive law. Addressing what is housing deal to know which is the reason why many people may not have your own and see the obligation of living leasing, is therefore necessary to include statistical data on the housing deficit existing in our city, all with data presented by the National Institute of statistics and censuses (INEC). Then describes the materials and methods used, for the realization of this research, the population and sample for the selection of respondents to proceed to issue the results of the surveys to 30 interviews 3 lawyers and law professionals. Is continuous with the verification objectives, said be incidentally all were checked, as was proven the hypothesis which turned out to be positive, and finally a legal analysis of the items considered obsolete, is made to issue the justification of proposed reform to the law of tenancy recommendations, all based on the results of field research, to culminate are giving the legal proposal to reform the law in question is badly needed